Asean's pivotal role for regional stability: a realist perspective within the context of Us-China rivalry in Southeast Asia - Suthan Venkatachalam; Ramli Dollah; Soo Siang Yang (University of Malaya, 2023)
Recent fieldwork in Terengganu, Peninsular Malaysia, resulted in the collection of an endemic new species of Ardisia, described here as Ardisia recurvipetala Julius, Siti-Munirah & Utteridge. The species is a member of subgenus (§) Crispardisia on account of its vascularised glands (bacterial nodules) on the leaf margin and the terminal inflorescence on a specialised lateral branch subtended by a normal leaf (rather than a reduced bract-like leaf). Ardisia recurvipetala is unique amongst all members of §Crispardisia by having leaf margins with both vascularised glands and pustule-like structures and can be further distinguished from other Peninsular Malaysian members of this subgenus by the lamina raised between the leaf venation giving a somewhat bullate appearance, unbranched inflorescences, brownish-red pedicels and recurved corolla lobes, each with a creamy-white apex and a small pink patch at the base. Ardisia recurvipetala is known only from a single location in Terengganu and its conservation status is assessed as Data Deficient (DD).